[Implementation of the ICD-ICF model in rehabilitation medicine: presentation of a clinical case in respiratory rehabilitation] - Lastoria, Cinzia; Cirio, Serena; Cirio, Raffaella; Ceriana, Piero; Vitacca, Michele (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2025)
We present the clinical case of a 74 years old patient undergoing tracheotomy for persistent hypercapnic respiratory failure after lower right lobectomy surgery, performed as a result of pulmonary cancer recurrence. The patient was transferred to the Department of Respiratory Sub Intensive Care for respiratory weaning, decannulation and cycle of motor and respiratory physiotherapy. The joint evaluation of physicians, nurses and physiotherapists has allowed the identification of ICD-9 and ICF codes of the severe disability shown by the patient in the first days of hospital stay (respiratory failure due to pneumonia that need invasive mechanical ventilation by tracheotomy, prolonged immobility, muscular deconditioning and inability to perform even the simplest activities of daily life; it required also artificial nutrition by naso gastric tube). ICF codes as respiratory functions (respiratory system functions, additional respiratory functions, sensations associated with cardiovascular and respiratory functions, moving with aids, walking, vestibular functions, muscle strength, tolerance to physical exercise, personal care, performing the routine daily sleep functions, energy and drive functions), were particularly compromised at admission. Medical intervention (antibiotic therapy based on microbiological isolations, optimization of inhalatory therapy, management of intestinal complications and cardiological which required cardiological treatment remodulation in order to obtain better heart rate control and better blood pressure control allowed a clear improvement of general and respiratory clinical conditions. The simultaneous physiotherapists' intervention (weaning not only from invasive mechanical ventilation but also from tracheotomic cannula and oxygen therapy, stationary and cycloergometer with arms and exercise training) and nurses'intervention (medication of pressure injuries, surveillance of the sleep-wake rhythm, management of the daily routine) allowed a gradual improvement of both motor and respiratory ability with a consequent indipendence in activities of daily living. Important were also psychological counseling and intervention of speech therapists (removal of naso gastric tube, once excluded dysphagia also by videofluoroscopy). During a long lasting clinical improvement, coincident with patient's discharge to home, has been assessed disability through ICF codes, largely improved under medical, nursing and physiotherapist profile.​